2006
DOI: 10.1007/s10826-005-9017-6
|View full text |Cite
|
Sign up to set email alerts
|

Violence Exposure and Early Adolescent Alcohol Use: An Exploratory Study of Family Risk and Protective Factors

Abstract: In this short-term longitudinal exploratory interview study, the relations between exposure to community violence and subsequent alcohol use were examined, with a focus on caregiver and family variables as moderators. Maternal caregivers and their children (N =101 families; 98% African American; M child age = 11.2 yrs) were interviewed separately and completed measures of violence exposure, caregiver and child adjustment, including substance use, and family functioning. Family interaction was also videotaped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
2
37
1
Order By: Relevance
“…A growing body of research has suggested that victimization, both witnessing violence (sometimes referred to as “indirect victimization”) and directly experiencing violence, increases the likelihood of smoking, drinking, and using illegal drugs among adolescents alcohol and other drug use (Kilpatrick et al, 2000; Kilpatrick et al, 2003; Lin et al, 2011; Sullivan et al, 2004; Taylor and Kliewer, 2006; Vermeiren et al, 2003; Zinzow et al, 2009). However, some literature suggests that substance use can increase victimization and/or that the two have reciprocal effects (Jennings et al, 2012; Thompson et al, 2008; Zhang et al, 2001), which emphasizes the need to examine the relationship using longitudinal data to better establish temporal ordering.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A growing body of research has suggested that victimization, both witnessing violence (sometimes referred to as “indirect victimization”) and directly experiencing violence, increases the likelihood of smoking, drinking, and using illegal drugs among adolescents alcohol and other drug use (Kilpatrick et al, 2000; Kilpatrick et al, 2003; Lin et al, 2011; Sullivan et al, 2004; Taylor and Kliewer, 2006; Vermeiren et al, 2003; Zinzow et al, 2009). However, some literature suggests that substance use can increase victimization and/or that the two have reciprocal effects (Jennings et al, 2012; Thompson et al, 2008; Zhang et al, 2001), which emphasizes the need to examine the relationship using longitudinal data to better establish temporal ordering.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Some studies have solely examined indirect victimization (Kliewer et al, 2006; Kliewer & Murrelle, 2007), others have focused only on direct victimization (Brady, Tschann, Pasch, Flores, & Ozer, 2009; Simantov, Schoen, & Klein, 2000), and some have combined indirect and direct victimization into a single measure of victimization (Buka et al, 2001; Thompson, Sims, Kingree, & Windle, 2008). The few studies that have examined both forms of victimization typically assess the impact of each independently (Albus, Weist, & Perez-Smith, 2004; Berenson, Wiemann, & McCombs, 2001; O'Donnell, Schwab-Stone, & Muyeed, 2002; Taylor & Kliewer, 2006; Vermeiren, Schwab-Stone, Deboutte, Leckman, & Ruchkin, 2003) and have rarely assessed the unique or relative effects of each of these different victimization experiences (but see Acosta, Albus, Reynolds, Spriggs, & Weist, 2001; Fowler, Tompsett, Braciszewski, Jacques-Tiura, & Baltes, 2009; Sullivan et al, 2007). Despite Agnew's (2002) suggestion that different victimization experiences should be controlled for simultaneously in statistical analyses to prevent overestimating the effects of one form of victimization, empirical studies have largely failed to do so.…”
Section: The Victimization/substance Use Relationshipmentioning
confidence: 99%
“…While the research on CONSEQUENCES OF EARLY EXPERIENCES OF VICTIMIZATION 569 consequences of property crime victimization is more limited, violent victimization has been related to posttraumatic stress disorder, substance abuse, and depression (Breslau, Davis, Peterson, & Schultz, 2000;Pimlott-Kubiak & Cortina, 2003;Taylor & Kliewer, 2006). Additionally, Koss and colleagues (1991) found victims' physician visits increased 13-22% more than nonvictims and that their overall health costs were 2.5 times greater due to adverse health effects of their victimization.…”
Section: Health Outcomes Of General Victimizationmentioning
confidence: 99%